Оценка повышения качества управления при переходе на линию МДУ - Кутовой, Юрий Николаевич; Кунченко, Татьяна Юрьевна (НТУ "ХПИ", 2010)
The paper shows advantages of tuning over a criterion of maximum Q factor and stability margin by means of a specially-developed control quality diagram technique. The technique provides subordinate control systems.
Fine tuning to maximum Q-factor and stability margin for a servo drive without subordinate speed loop
Keywords: электропривод; регулятор; добротность максимальная; запас устойчивости; система подчиненного регулирования